EFEKTIFITAS PENYULUHAN METODE DEMONSTRASI BREAST CARETERHADAP PENINGKATAN PENGETAHUAN PADA IBU HAMIL - Maryono, Maryono; Bustami, Bustami; Khairunnisak, Khairunnisak (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Global exclusive breastfeeding rates, despite an increase, have not risen significantly enough, with approximately 44% of infants aged 0-6 months worldwide receiving exclusive breastfeeding during the 2015-2020 period, compared to the WHO target of 50%. The low rate of exclusive breastfeeding will have an impact on the quality and life expectancy of future generations. Breast care has a positive effect on increasing breast milk production; therefore, breast care needs to be implemented by pregnant and postpartum mothers. There are various ways to improve breast care skills among pregnant and postpartum women, one of which is through demonstration. This study aims to determine and analyze the effectiveness of demonstration methods in increasing knowledge about breast care among pregnant women. This study used a quasi-experimental design. Data collection was conducted using questionnaires. There were 30 respondents in this study. The results showed that there was an increase in knowledge about breast care from before the demonstration with an average score of 5.8 to 8.37 after the demonstration. The Wilcoxon Signed Ranks Test showed that the p-value was 0.000 (p<0.05). It is recommended that health workers provide health education using the breast care demonstration method to increase the knowledge of pregnant women.